Proceso de atención enfermería en paciente de 53 años con tuberculosis pulmonar y anemia severa. - Veliz Pino, Geovanny Alejandro (2023)
Tuberculosis disease caused by Mycobacterium is transferred from person to person Tuberculosis can occur in three stages, primary, active and latent infection. Usually before signs or symptoms appear such as weight loss, hemoptysis, cough for more than 15 days, the medication in the first phase lasts for 6 months distributed in 2HRZE/4HR and HRZE in 9 months due to loss of follow-up. Anemia is a condition in which the number of red blood cells or the hemoglobin concentration among them is lower than normal. The symptoms that the patient with anemia can manifest can be very multiple, depending fundamentally on the etiological process and also on the speed of onset. Through which the PAE was applied systematically with the help of the NANDA, NOC and NIC taxonomy to use a diagnosis that was nursed and then implement the care plan to cover all their needs in a timely manner according to the previously manifested pathology.